Tingkat Pengetahuan Wajib Pajak Pada Kepatuhan Membayar Pajak Di Kabupaten Sorong - Kamila Maulidiya Nisak; Pahmi Pahmi; Munzir Munzir (Program Studi Akuntansi Unimuda Sorong, 2024)
The purpose of this study was to see the effect of the level of taxpayer knowledge on compliance with paying taxes. This study discusses the level of compliance of taxpayers in paying taxes in the Sorong Regency area. Based on observations that have been made before conducting this research, researchers see that there is still low compliance and knowledge of taxpayer to carry out their tax obligations in accordance with tax regulations, so researchers are interested in conducting research on this topic. This study uses a quantitative approach, the sampling of this study uses the Slovin formula, the sample size is 99 individual taxpayer repondents. The results of this study indicated that the level of knowledge of taxpayers has a positive and significant effect on tax compliance in Sorong Regency. The most basic thing that every taxpayer has is knowledge, because without knowledgxation, it will make it difficult for taxpayers to carry out their tax obligations. Taxpayers who have good knowledge of tax regulations and obligations are more likely to understand the importance of paying taxes.